Progressive Encephalomyelitis with Rigidity and Myoclonus with an Aggressive Presentation Mimicking Septic Shock: A Pediatric Case Report and Literature Review - Ho, Samuel C.S.; Leung, K. Y.; Ng, Grace S.F.; Yiu, W. L.; Yau, Eric K.C.; Fong, N. C. (Journal of Pediatric Neurology, 2023)
Progressive encephalomyelitis with rigidity and myoclonus (PERM) is a relapsing–remitting neurological disorder that falls within the stiff person syndrome–spectrum disorders. We report a 16-year-old girl with PERM associated with an anti-glutamic acid decarboxylase (GAD) antibody. She had an aggressive initial presentation mimicking fulminant septic shock, followed by truncal and lower limb rigidity, stimulus-sensitive spasm, cognitive impairment, brainstem signs (hyperekplexia, nystagmus), and dysautonomia (urinary retention, constipation, facial flushing, blood pressure fluctuation). Cerebrospinal fluid, electroencephalography, and magnetic resonance imaging of the brain and spine showed features suggestive autoimmune encephalitis and myelitis. The serum anti-GAD antibody was positive, and the diagnosis of PERM was made. She had fluctuating clinical response despite intravenous immunoglobulin, steroids, plasmapheresis, and symptomatic medications. Eventually, in the fourth month since admission, she showed gradual and persistent clinical improvement after introducing rituximab. She was discharged after 6 months of hospitalization, and no relapse was observed in the first 3 years of follow-up.PERM is a rare and underrecognized condition in children. Contrary to previous reports, our case describes an aggressive and life-threatening presentation for PERM. Vague symptoms and the lack of gold diagnostic tests hinder a timely diagnosis. Our study also highlights the need for developing standardized diagnostic criteria and consensus in managing PERM.
Keywords: PERM; stiff person syndrome; glutamic acid decarboxylase; dysautonomia